Epidemiological factors for development/progression of downy mildew (Peronospora alta) on blond psyllium (Plantago ovata) - RATHORE*, B.S. (Indian Phytopathology, 2008)
Occurrence of downy mildew (Peronospora alta Fuckel) on blond psyllium (Plantago ovata Forsk.) is greatly influenced by various factors. For initial development of downy mildew sufficient inoculum (105 conidia/ml) couple with susceptible age of plant (70-80 days old plant), low temperature (15 and 20o C for 48 h) with high relative humidity (100% for 96 h) was found essential. Five-year field study was conducted to ascertain the role of different climatic factors for the development and progression of downy mildew in blond psyllium in order to develop a prediction models. Average time taken for the appearance of initial symptoms of downy mildew was 54 days after planting. Average apparent infection rate (r) was 0.0931 units/day while secondary spread and maximum infection was 57.0% and 59.6%, respectively. Progress of disease was gradual during initial phase but soon it was followed by a spread at compound interest rate until a plateau was reached. Temperature (max. and min.) was positively correlated but relative humidity was negatively correlated with the development of disease.